2016
DOI: 10.1007/s00441-016-2422-x
|View full text |Cite
|
Sign up to set email alerts
|

Extrinsic innervation of ileum and pelvic flexure of foals with ileocolonic aganglionosis

Abstract: Equine ileocolonic aganglionosis, which is also called lethal white foal syndrome (LWFS), is a severe congenital condition characterized by the unsuccessful colonization of neural crest progenitors in the caudal part of the small intestine and the entire large intestine. LWFS, which is attributable to a mutation in the endothelin receptor B gene, is the horse equivalent of Hirschsprung's disease in humans. Affected foals suffer from aganglionosis or hypoganglionosis of the enteric ganglia resulting in intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In horses, most of the SP‐IR innervation derives from enteric neurons supplying the CML (Figure G) . Double immunohistochemistry carried out on adult horse tissues showed that 5‐HT 4 ‐ and SP‐IR fibers widely co‐localized (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In horses, most of the SP‐IR innervation derives from enteric neurons supplying the CML (Figure G) . Double immunohistochemistry carried out on adult horse tissues showed that 5‐HT 4 ‐ and SP‐IR fibers widely co‐localized (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Lumbar spinal ganglia were collected from the half‐carcasses. Furthermore, the ileum and pelvic flexure of two new‐born American paint male foals affected with LWFS were utilized . According to Directive 2010/63/EU of the European Parliament and of the Council of September 22, 2010 on the protection of animals used for scientific purposes, the Italian legislation (D. Lgs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations